The role of scaffolding in shaping reflective mathematical thinking of dependent field students in numeracy problems - Setiyani, Setiyani; Gunawan, Gunawan; Waluya, Stevanus Budi; Sukestiyarno, Yohanes Leonardus; Cahyono, Adi Nur; Mutia, Mutia; Yunianto, Wahid (IKIP Siliwangi and I-MES, 2025)
In learning mathematics, reflective thinking is often overlooked due to an excessive emphasis on final results, which causes students to struggle in evaluating and reconstructing their problem-solving processes. Reflective thinking skills are necessary for students to solve problems, including numeracy. This study adopts a qualitative approach, focusing on the problem-solving process of two seventh-grade students with a Dependent Field (DF) cognitive style and similar initial mathematical abilities. Data were collected through the Group Embedded Figures Test, in-depth interviews, and initial mathematical and reflective thinking ability tests. Based on the research results, DF students couldn't analyze arguments from various perspectives and see if there were deeper implications. This finding reflects the characteristics of DF, who don't perform the 'result in context' process, leading to a lack of ability to understand, interpret, and use numerical results in concrete/situational contexts. This also includes the ability to relate numbers to real-world situations, make appropriate interpretations, and take suitable actions based on those numerical results. The results of this study can serve as a foundation for designing differentiated instruction that emphasizes the development of reflective thinking skills, particularly in numeracy, through approaches involving technology, models, pedagogy, or other learning strategies.